SDG-aligned futures and the governance of the transformation to sustainability reconsidering governance perspectives on the futures we aspire to - Ariel Hernandez (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
The (im)possibility of governance of the transformation to sustainability (T2S) is driven by how the related multiple transition processes as well as the various functional, institutional and bargaining interactions among relevant agents or stakeholders can be steered. Like other transformation processes, T2S is an immediate response to threats and risks behind structural changes. In addition, T2S is a 'purposive new normal' because it seeks ways to achieve a new equilibrium whereby the system is able to effectively confront or prevent imminent threats and risks. At the same time, this paper claims that there can be more than one version of the new equilibrium for each state or society. This paper argues against the 'ahistoricity' (Geschichtslosigkeit) approach of much of the literature on T2S and contends that each country has a distinct set of socio-political (e.g. quality of institutions) and economic resources (e.g. gross national income) available, depending on its current standing. [...]
Keywords: 330